Correlation Between Spiritual Intelligence and Self-efficacy Patients with Coronary Artery Disease - Wantiyah Wantiyah; Wiwit Ulansari; Fitrio Deviantony (Faculty of Nursing Universitas Padjadjaran, 2020)
Coronary Heart Disease (CHD) is a cardiovascular disease affecting the patient’s life both psychologically and physically. Therefore it can reduce patients’ quality of life. Self-efficacy is one crucial factor that can improve the quality of life of patients with CHD to control risk factors. spiritual intelligence can make a person more able to interpret the life and have a positive meaning in each event, to improve the quality of life. This study used a descriptive correlation research design with a cross-sectional approach. This research involved 138 CHD patients as respondents in RSD dr. Soebandi of Jember, East Java, Indonesia, obtained by accidental sampling method. Data were collected using a Spiritual Intelligence questionnaire and Cardiac Self-Efficacy (CSE). The analysis of data used is Somers’d test with a confidence level of 95% (α: 0.05). Respondent characteristics include age, gender, marital status, education, occupation, income, smoking history, and disease history. The results showed that 86.2% of CHD patients had high self-efficacy, and 55% of CHD patients had high spiritual intelligence. Analysis shows there is a strong correlation between spiritual intelligence and self-efficacy (p = <0.001, r = 0.628, α: 0.05). The patients having high spiritual intelligence will have high self-efficacy. Spiritual intelligence comes from within the patient, which can be developed to improve the self-efficacy of CHD patients through the provision of holistic nursing care. Therefore, it is expected for nursing staff to assess patients’ spiritual intelligence, so they can provide appropriate nursing care so that patient self-efficacy can be improved, and patient health can be optimized.